Characterization of three salmon louse (Lepeophtheirus salmonis) genes with fibronectin II domains expressed by tegumental type 1 glands. - Harasimczuk, E., A.C. Øvergard, S. Grotmol, F. Nilsen & S. Dalvin (Molecular and Biochemical Parasitology, 2018)
The salmon louse, Lepeophtheirus salmonis (Copepoda: Caligidae), is currently the most significant pathogen affecting the salmon farming industry in the Northern Hemisphere. Exocrine glands of blood-feeding parasites are believed to be important for the host-parasite interaction, but also in the production of substances for integument lubrication and antifouling. In L. salmonis; however, we have limited knowledge about the exocrine glands. The aim of this study was therefore to examine three genes containing fibronectin type II (FNII) domains expressed in L. salmonis tegumental type 1 (teg 1) glands, namely LsFNII1, 2 and 3. LsFNII1, 2 and 3 contains four, three, and two FNII domains respectively. Sequence alignment of LsFNII domains showed conservation of amino acids that may indicate a possible involvement of LsFNII domains in collagen binding. Ontogenetic analysis of LsFNII1, 2 and 3 revealed highest expression in pre-adult and adult lice. Localization of LsFNII1, 2 and 3 transcripts showed expression in teg 1 glands only, which are the most abundant exocrine gland type in L. salmonis. LsFNII1, 2 and 3 were successfully knocked-down by RNAi, however, alteration in gland morphology was not detected between the knock-down and control groups. Overall, this study gives first insight into FNII domain containing proteins in L. salmonis.